Determination of Heavy Metals in the Shrimp (Farfantepenaeus paulensis) Consumed in the City of Pelotas-RS - Parodes Pinto, Ane Martiele Taborda; Hirdes, Inês Moraes; Sanches Filho, Pedro José (Ecotoxicology and Environmental Contamination, 2013)
The objective of this study was to evaluate the heavy metal contamination in shrimp ́s species Farfantepenaeus paulensis consumed in Pelotas - RS, obtained from the places that they are usually fished: the Atlantic Ocean and Laguna dos Patos in South Brazil. The analyses were performed in the muscle tissue and the exoskeleton, at two different times. The samples were perchloric nitric acid digestion, and the determination of cadmium, lead, copper and zinc spectrometry carried out by flame atomic absorption. To control the accuracy and recovery was analyzed certified reference material DORM-3 showing recoveries of 71.2% to 98.8%. The concentrations were determined only for Pb, Cu and Zn. Particularly, the Pb in one of the exoskeleton sample had its level above of the limit allowed by law. Shrimps collected in the Patos Lagoon had higher levels of contamination, although it was proven that the exoskeleton has more concentrated levels of metals. The results also suggest that the region of Patos Lagoon has increased availability of zinc and lead.